In-flight thermal experiments for LISA Pathfinder: Simulating temperature noise at the Inertial Sensors. (April 2015) - Gibert, F; Nofrarias, M; Armano, M; Audley, H; Auger, G; Baird, J; Binetruy, P; Born, M; Bortoluzzi, D; Brandt, N; Bursi, A; Caleno, M; et al.
Abstract: Thermal Diagnostics experiments to be carried out on board LISA Pathfinder (LPF) will yield a detailed characterisation of how temperature fluctuations affect the LTP (LISA Technology Package) instrument performance, a crucial information for future space based gravitational wave detectors as the proposed eLISA. Amongst them, the study of temperature gradient fluctuations around the test masses of the Inertial Sensors will provide as well information regarding the contribution of the Brownian noise, which is expected to limit the LTP sensitivity at frequencies close to 1 mHz during some LTP experiments. In this paper we report on how these kind of Thermal Diagnostics experiments were simulated in the last LPF Simulation Campaign (November, 2013) involving all the LPF Data Analysis team and using an end-to-end simulator of the whole spacecraft. Such simulation campaign was conducted under the framework of the preparation for LPF operations.